PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN VIDEO PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PEMANASAN GLOBAL - Dwika Septiarini, Rizki; Sri Murti Rahayu, Ridha; Anggraini, Julia; Yusal, Yulianti; Anggraini, Atika (Ikatan Keluarga Alumni FKIP Universitas Tanjungpura, 2024)
Traditional learning that tends to be teacher-centered causes students to have difficulty linking theory with real life, so an innovative approach that encourages student activeness is needed, such as PBL combined with learning videos. This study aims to examine the effectiveness of applying the Problem Based Learning (PBL) model assisted by learning videos in improving student learning outcomes on global warming material. The research was conducted using the Classroom Action Research (PTK) method with participants of VII B class students totaling 28 students on global warming material at the junior high school level. With a learning achievement test based on Bloom's taxonomy (C1-C4). Cycle I used lecture-type videos, while Cycle II used animated videos, with data measured using learning outcomes tests. The results showed an increase in the average student learning outcomes from 5.53 in Cycle I to 7.53 in Cycle II. In addition, the number of students who reached the KKM increased from 7 students to 19 students. Thus, the application of the PBL model assisted by learning videos is effective in improving student learning outcomes on global warming material